CHARACTERIZATION OF SORBENT PRODUCED THROUGH IMMOBILIZATION OF HUMIC ACID ON CHITOSAN USING GLUTARALDEHYDE AS CROSS-LINKING AGENT AND Pb(II) ION AS ACTIVE SITE PROTECTOR - Uripto Trisno Santoso; Sri Juari Santosa; Dwi Siswanta; Bambang Rusdiarso; Shogo Shimazu (Universitas Gadjah Mada, 2010)
Sorbent produced through immobilization of humic acid (HA) on chitosan using glutaraldehyde as cross-linking agent and Pb(II) ions as active site protector has been characterized. Active sorption site of HA was protected by reacting HA with Pb(II) ion, and the protected-HA was then activated by glutaraldehyde, crosslinked onto chitosan, and deprotected by 0.1 M disodium ethylenediamine tetra-acetic acid (Na2EDTA). The protected-crosslinking method enhanced the content of immobilized-HA and its chemical stability. Based on the FTIR spectra, crosslinking of HA on chitosan probably occurred through a chemical reaction. The sorption capacity of sorbent still remains unchanged after the second regeneration, but some of HA start to be soluble. The latter shows that cross-linking reaction between HA and chitosan is through formation an unstable product. The effectiveness of sorbent regeneration can also be identified by the XRD pattern.